2014
DOI: 10.1186/2193-1801-3-677
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and larval developmental stages of African giant catfish Heterobranchus bidorsalis (Geoffroy Saint Hilaire, 1809) (Teleostei, Clariidae)

Abstract: The dearth of African giant catfish Heterobranchus bidorsalis seeds poses great threat to its aquaculture and biodiversity, hence detailed knowledge and understanding of its embryology is indispensable for its artificial propagation and conservation programmes. Photomicrographs of extruded oocyte through all developmental cell stages of live embryo to larval stage are documented with the aid of a light microscope. The optical transparency of the developing embryo enabled us to describe its deep structures, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…The hatching in fish is facilitated by muscular contraction or twitching at caudal part (Honji et al., ; Olaniyi & Omitogun, ). In this study, vigorous movement of caudal part broke down perivitelline membrane at tail region and hatchling emerged out as tail first, which is similar to the observations made in M. montanus (Arockiaraj et al., ), H. fossilis (Puvaneswari et al., ) and H. bidorsalis (Olaniyi & Omitogun, ). However, Langeland and Kimmel () opined that during hatching, head comes out first and tail comes out last from the embryo in most of the teleosts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The hatching in fish is facilitated by muscular contraction or twitching at caudal part (Honji et al., ; Olaniyi & Omitogun, ). In this study, vigorous movement of caudal part broke down perivitelline membrane at tail region and hatchling emerged out as tail first, which is similar to the observations made in M. montanus (Arockiaraj et al., ), H. fossilis (Puvaneswari et al., ) and H. bidorsalis (Olaniyi & Omitogun, ). However, Langeland and Kimmel () opined that during hatching, head comes out first and tail comes out last from the embryo in most of the teleosts.…”
Section: Discussionsupporting
confidence: 90%
“…Olaniyi and Omitogun () reported polster and tail bud as markers for the identification of cranial and caudal parts, respectively, during neurulation. This study revealed distinct neurulation and segmentation period in M. gulio , which is similar to the observation of Olaniyi and Omitogun () in H. bidorsalis , but in contrary to the report of Kimmel et al. () in Denio rerio .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Clarias gariepinus (Burchell, 1822) and Heterobranchus bidorsalis (Geoffroy Saint Hilaire, 1809) are of high economic importance in many countries of the world especially African and Asian continents (Legendre et al. ; Adebayo and Fagbenro ; Olaniyi and Omitogun , ); and also serve mainly as food in many homes and hotels (Omitogun et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the same stages of C. magur embryos incubated at water temperature of 25–29 °C was observed to be delayed by 15 min (2-cells stage) to 1 h (somite stage) after the fertilization (Table 2). Usually, such differences in embryonic development in teleost fish species occur because of the incubation water temperature (Olaniyi and Omitogun, 2014); the higher the water temperature, the faster is the embryonic development and hatching (Hogendoorn and Vismans, 1980). The most salient result obtained in this study is successful hatching of 88%–92% embryos obtained from dead donors compared to 92%–93% from live control.…”
Section: Resultsmentioning
confidence: 99%